2016
DOI: 10.1002/gcc.22341
|View full text |Cite
|
Sign up to set email alerts
|

Complex chromosomal rearrangements leading to MECOM overexpression are recurrent in myeloid malignancies with various 3q abnormalities

Abstract: Chromosomal rearrangements involving 3q26 are recurrent findings in myeloid malignancies leading to MECOM overexpression, which has been associated with a very poor prognosis. Other 3q abnormalities have been reported and cryptic MECOM rearrangements have been identified in some cases. By fluorescence in situ hybridization (FISH) analysis, we investigated 97 acute myeloid leukemia/myelodysplastic syndrome patients with various 3q abnormalities to determine the role and the frequency of the involvement of MECOM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 39 publications
0
7
0
1
Order By: Relevance
“…Altered MECOM gene expression is commonly associated with initiation and aggressiveness in a variety of hematologic cancers (15). To assess if MECOM expression perturbations are common in other cancer types, we examined MECOM gene expression using RNA-seq data obtained from TCGA from a variety of solid tumor types.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Altered MECOM gene expression is commonly associated with initiation and aggressiveness in a variety of hematologic cancers (15). To assess if MECOM expression perturbations are common in other cancer types, we examined MECOM gene expression using RNA-seq data obtained from TCGA from a variety of solid tumor types.…”
Section: Resultsmentioning
confidence: 99%
“…It is well established that chromosomal aberrations at the PRDM3-encoding gene, MECOM , are found in up to 10% of AML cases with poor survival outcomes (13,14). The expression levels of specific MECOM isoforms suggests that the N-terminal residues of PRDM3 bestow a tumor suppressor function, while the oncogenic shorter EVI1 isoform is overexpressed in myeloid, ovarian, liver and colon tumors, and correlates with poor outcome in AML (1,12,13,15–18). Indeed, this is supported by our comparative analysis of MECOM isoform expression between patient-matched tumor and healthy tissues and identified a previously unreported loss of full-length PRDM3 expression as a common feature of certain solid tumor types, such as renal, lung, prostate and breast carcinomas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through the experiment of the study, all patients with MECOM amplification showed MECOM mRNA overexpression with a range of 2.6-54.4, whereas the median MECOM mRNA expression in patients without MECOM rearrangement/amplification was of a range 0.01-0.58 [18]. This indicates that there is a significant correlation between MECOM amplification and the MECOM mRNA overexpression [18]. In addition, amplified MECOM is associated with ovarian cancer [19].…”
Section: Discussionmentioning
confidence: 93%
“…The previous study identified that the MECOM amplification had been observed at myeloid malignancies and that MECOM amplification associated with MECOM mRNA overexpression [18]. Through the experiment of the study, all patients with MECOM amplification showed MECOM mRNA overexpression with a range of 2.6-54.4, whereas the median MECOM mRNA expression in patients without MECOM rearrangement/amplification was of a range 0.01-0.58 [18]. This indicates that there is a significant correlation between MECOM amplification and the MECOM mRNA overexpression [18].…”
Section: Discussionmentioning
confidence: 99%